2012
DOI: 10.1080/02571862.2012.740506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liming and inorganic fertiliser application on soil properties and maize growth and yield in rural agriculture in the Mbizana area, Eastern Cape province, South Africa

Abstract: A five-year study was conducted to assess the seasonal and medium-term effects of liming and fertilisation of an acid clay loam topsoil on soil properties and on the growth and yield of maize under dry land. Treatments consisted of a control, a once-off application of three levels of dolomitic lime, annual application of two levels of inorganic fertiliser, and three levels of chicken manure. A no-till practice was used with hand planting and fertiliser application. Leaf and soil sampling, as well as harvesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…With liming, increased Ca concentration in grain may indicate the increase in crop growth and yield due to the amelioration of Al toxicity. This in agreement with finding by Beukes et al (2012) who reported that liming increased the Ca concentration in grain of maize crop. The high Cain grain wheat concentration with higher lime rate provides the soil have high soil exchangeable Ca attributed to improved Ca concentration in the soil (Bolanet al 2003).…”
Section: Discussionsupporting
confidence: 93%
“…With liming, increased Ca concentration in grain may indicate the increase in crop growth and yield due to the amelioration of Al toxicity. This in agreement with finding by Beukes et al (2012) who reported that liming increased the Ca concentration in grain of maize crop. The high Cain grain wheat concentration with higher lime rate provides the soil have high soil exchangeable Ca attributed to improved Ca concentration in the soil (Bolanet al 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, plants release excess H + when cation uptake exceeds anion uptake . The decrease in pH with NPK application was also observed by Ogundijo et al (2015) and Beukes et al (2012).…”
Section: Effects Of Lime and Npk Fertilizer On Soil Phsupporting
confidence: 52%
“…Liming is one of the most common practices to ameliorate acid soil, with many wellunderstood benefits. It causes the reduction of Al and Mn toxicity [9,10], maximizes nutrient availability for plants [11,12], decreases P immobilization [13], improves physical [14] and biological soil quality [15], and enhances crop production. Liming also enhances the C sequestration rate of both minerally fertilized and organically manured plots [16].…”
Section: Introductionmentioning
confidence: 99%